A evidenciação de informações contábeis obrigatórias e voluntárias: um estudo em clubes de futebol brasileiros - Mayer, Rafael (Universidade do Vale do Rio dos Sinos, 2017)
Nowadays, Brazilian professional soccer is responsible for significant financial transactions, and the way these are presented can attract many investors to the sports market. Considering the relevance of transparent financial disclosures to the Brazilian professional soccer teams, this work developed a study about the factors that are related to the forms of financial disclosures. For that purpose, the financial disclosures of 22 soccer clubs concerning the years from 2012 to 2015 were analyzed. This research was based on the resolution CFC nº 1.429, January 25, 2013, which acknowledges ITG 2003 – Professional Sports Entity. Applying the methods of Descriptive Statistics and the Pearson Correlation Coefficient, the indexes of Obligatory, Voluntary and Total Disclosure Rates were tested. Initially, each index was tested individually according to its year, and after that the average index was calculated. As a result, the Index of Obligatory Disclosure Rate obtained was 65,70%; the Voluntary Disclosure Rate obtained was 7,10%; and the Total Disclosure Rate obtained was 42,30%. After the analysis of the correlation and the hypothesis tests, it was found that soccer clubs with the best Indexes of Disclosure presented the following features: most of them were run by CEOs with a Law Degree; such teams have the best sports performance attested by the CBF Ranking; these clubs also have the best financial performance, rated by the EBITDA (Earnings Before Interests, Taxes, Depreciation and Amortization) margin. It was also stated that the clubs with higher revenues, asset values and intangible values show the best disclosure indexes. During the analysis, the indexes of disclosure presented significant improvements, considering that in the last year the index of obligatory disclosure in some clubs had a compliance rate to the ITG 2003 requirements of 94%. It is perceived an improvement on the clubs transparency and the search for a better legitimacy to the associates, supporters and users of the financial disclosures.
Keywords: Clubes de futebol; Evidenciação; Transparência; Legitimidade; Soccer clubs; Disclosures; Transparency; Legitimacy; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis